1092. Population Pharmacokinetics of Cephalexin in Non-Obese and Obese Hospitalized Patients with Infectious Diseases. (4th December 2021) - Jeong, Kyeoul; Chung, Eun Kyoung; Cheatham, S Christian; Stock, Andrea H; Utley, Sara; Healy, Daniel P; Campion, Maureen G; Murrey, Timothy; Gesenhues, Alicia M; Jeffery, Julia; Kays, Michael B
Abstract: Background: Obesity is a significant global health problem and has been associated with altered pharmacokinetics (PK) and pharmacodynamics (PD) of many drugs. Cephalexin is a commonly prescribed antibiotic as an oral drug for the treatment of mild to moderate infections; however, little is known regarding cephalexin pharmacokinetics in obese patients. The objective of this study was to investigate the population PK of cephalexin in non-obese and obese patients. Methods: Hospitalized patients who were 18 years or older with a suspected or documented infection were studied. Patients weighing < 120 kg were defined as non-obese patients whereas those weighing ≥ 120 kg as obese. All included patients received cephalexin 1000 mg every 6 hours orally. After ≥ 3 days of therapy, serial blood samples were collected. Ultrafiltration was used to separate the unbound drug from the protein-bound fractions, and both total and unbound serum concentrations were determined by HPLC. The concentration-time data for cephalexin were analyzed by a non-linear mixed effects modeling approach using NONMEM. Results: Overall, 255 serum concentrations from 19 patients (10 males, 4 in an ICU) were included; ten patients were non-obese (total body weight [TBW] < 120 kg) and nine were obese (TBW ≥ 120 kg). A 1-compartment model with first-order absorption, absorption lag-time, first-order elimination, and linear protein binding best fit the concentration-time data. Creatinine clearance (CrCl) was the only covariate significantly associated with cephalexin PK, specifically systemic clearance (CL): CL (L/h) = 12.3 + [0.0837*(CRCL – 81.8)]. No other covariates significantly affected the model-derived PK parameters including CL, volume of distribution (V), first-order absorption rate constant (Ka ), unbound fraction ( f u ) with the fixed estimate of 0.776, and absorption lag-time (Tlag ). Conclusion: In conclusion, cephalexin PK is comparable between non-obese and obese patients. Dosing adjustments based solely on body size may not be necessary. Further analyses are warranted to suggest optimal cephalexin dosages in obesity through large-scale population PK-PD modeling and simulation. Disclosures: All Authors : No reported disclosures